A Study on Causes and Impacts of Disputes on Selected Road Construction Contracts under Department of Roads, Nepal - Dhakal, Anju (Everest Advances in Science and Technology, 2025)
Construction projects, particularly road projects, are highly susceptible to disputes, leading to significant negative consequences. This research aimed to categorize road project disputes by severity, identify their root causes, analyze their impacts on contracts, and explore mitigation strategies. Data were collected through questionnaires distributed to 112 respondents, with an 82.14% response rate, and analyzed to determine major dispute causes, their effects, and potential solutions. Spearman’s rank correlation was used to assess stakeholder (employer, consultant, contractor) perceptions. The study revealed that disputes primarily arise from land acquisition challenges, forest clearing delays, resettlement issues, mismanagement of contract terms, and fluctuations in labor, material, and equipment costs. These disputes severely impact road contracts, causing project delays, cost overruns, strained stakeholder relationships, reputational damage, and even project failure. To minimize such disputes, the study emphasizes fostering a trustworthy project environment, ensuring timely issue resolution, approving and delivering drawings promptly, and meeting other critical requirements. Proactive measures, such as clear contract documentation, effective communication, and stakeholder collaboration, are essential to reducing claims and disputes in future road projects. By addressing these key factors, construction stakeholders can enhance project efficiency, maintain harmonious relationships, and safeguard public image while ensuring successful project delivery. The findings underscore the importance of dispute prevention strategies to mitigate risks and improve overall project outcomes in the road construction sector.